Effect of Dietary Counseling in Chronic Renal Failure Patients on Hemodialysis - Maurya, Neelesh Kumar (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The present study was conducted with the aim to assess and analyze the effect of dietary counseling the nutritional status of patients (>19 years) undergoing hemodialysis (HD) at least 3 months and in chronic kidney disease (CKD)-5 stage for the past 3 months. Materials and Methods: A total of 60 subjects were enrolled in the study (48 males and 12 females) in two groups; the first group taken proper medication and dialysis therapy and the second one additional diet counseling we suggested soy and paneer-like high biological protein. Different biochemical parameters such as blood urea, creatinine, and albumin along with the amount of calorie and protein intake were compared pre-nutritional counseling and post-nutritional counseling and protein dietary recommendation for 60 days during ongoing HD. Results: Short-term suggestion resulted in a significant statistically difference in the biochemical parameters. Proper dietary counseling along with high biological protein (1.2 gm/kg/ideal body weight) is given during HD superior the nutritional status of undernourished CKD patient. About proper diet counseling of the patients showed a positive response (<0.005) while the only medication and dialysis therapy showed an undergoing undernourished in their nutritional status. Conclusion: Patients undergoing HD frequently develop protein-energy malnutrition which is related to morbidity and mortality rate increases. Special nutritional care is required for the dialysis patient to improve the net protein anabolism.